AChRs Degeneration at NMJ in Aging-Associated Sarcopenia–A Systematic Review - Bao, Zhengyuan; Cui, Can; Chow, Simon Kwoon-Ho; Qin, Ling; Wong, Ronald Man Yeung; Cheung, Wing-Hoi (Frontiers in Aging Neuroscience, 2020)
Sarcopenia is an ageing process with a decline of skeletal muscle mass and function, which is a challenging public health problem with reduced quality of life in patients. The endplate, the post-synaptic part of the neuromuscular junction (NMJ), occupies 0.1% of the myofiber surface area only, but is composed of millions of acetylcholine receptors (AChRs) that are efficient in binding to acetylcholine (ACh) and triggering skeletal muscle contraction. This systematic review aims to examine ageing-associated alterations of post-synaptic AChRs, including morphology, function and related gene expression. A systematic literature search was conducted in PubMed, Embase and Web of Science with relevant keywords by two independent reviewers. Original pre-clinical and clinical studies regarding AChRs changes during ageing with available full text and written in English were included. Information was extracted from the included studies for further review. In total, 30 articles were included. Various parameters assessing AChRs alterations by radioassay, immunofluorescence, electrophysiology and mechanical test were reported. Endplate fragmentation and denervation were common in old skeletal muscles during ageing. To ensure efficient NMJ transmission and force generation, type I or IIb muscle fibers tended to have increased ACh quanta releasing after electrical stimulations, while type IIa muscle fibers tended to have stronger binding between ACh and AChRs, but the overall function of AChRs was reduced during ageing. Alterations of AChRs area depended on muscle type, species and the progress of muscle atrophy and type I muscles fibers tended to demonstrate enlarging AChRs areas. Myogenic regulator factors (MRFs) can regulate the expression of AChRs subunits, while decreased MRF4 may lead to expression changes of AChRs subunits during ageing. Sarcoglycan-α can delay low-density lipoprotein receptor-related protein 4 (LRP4) degradation. This protein was increased in old muscles but still cannot suppress the degradation of LRP4. Investigating the role of these AChRs-related genes in the process of ageing may provide a potential target to treat sarcopenia.